2010
DOI: 10.1089/jmf.2008.1212
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cardiovascular Protective Effects of Tropical Seaweeds, Kappaphycus alvarezii, Caulerpa lentillifera, and Sargassum polycystum, on High-Cholesterol/High-Fat Diet in Rats

Abstract: This study was designed to investigate the comparative in vivo cardiovascular protective effects of red, green, and brown tropical seaweeds, namely, Kappaphycus alvarezii (or Eucheuma cottonii), Caulerpa lentillifera, and Sargassum polycystum, in rats fed on high-cholesterol/high-fat (HCF) diets. Male Sprague-Dawley rats (weighing 260-300 g) on the HCF diet had significantly increased body weight, plasma total cholesterol (TC), plasma low-density lipoprotein cholesterol (LDL-C), plasma triglycerides (TG), lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 29 publications
2
57
1
2
Order By: Relevance
“…The resultant supernatant was used for various biochemical assays. The homogenate protein content was determined (Matanjun, Mohamed, Muhammad, & Mustapha, 2010), by calibrating with bovine serum albumin.…”
Section: Animal Studiesmentioning
confidence: 99%
“…The resultant supernatant was used for various biochemical assays. The homogenate protein content was determined (Matanjun, Mohamed, Muhammad, & Mustapha, 2010), by calibrating with bovine serum albumin.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Numerous studies have shown that methanol, ethanol and aqueous extracts of P. palmata exhibit antioxidant activity [19][20][21]. Red seaweeds have also been shown to exhibit hypolipidemic activity favourably altering lipid profiles in animal models [22,23].…”
mentioning
confidence: 99%
“…The antioxidant potential of numerous edible seaweeds was found to be remarkably high [34]. Cardioprotective roles of red, brown, and green algae have also been established recently [35]. Subashini et al [36] have earlier proved the antihyperglycemic effect of different extracts of G. corticata in STZ-induced diabetic and normal rats.…”
Section: Resultsmentioning
confidence: 99%